REPRESENTASI NILAI-NILAI AGAMA DALAM FILM DOKUMENTER INDONESIA BUKAN NEGARA ISLAM KARYA JASON ISKANDAR - Muhammad Rahmad Luhur; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Indonesia is not an Islamic State is a documentary about the work of Jason Iskandar, where the documentary film making occurred inadvertently caused by the Director's own bad experience. The documentary, Indonesia is not an Islamic State tells the story of two muslim student who attended private catholic school in jakarta, where they see based on their respective points of view that Indonesia is getting increasingly mixed into an Islamic State, and is assosiated with events that occurred on June 1, 2008 about the storming of FPI (Islamic Defenders Front) against AKKBB (National Alliance for freedom of religion and Believe). This research is a descriptive study of qualitative approach to the analysis of the semiotics of Charles Sanders Peirce. The objec of his research is the impressions documentary film Indonesia is not an Islamic State which lasted 9 minutes 32 second which have been published in 2009. The results obatained from the analysis of the top film Indonesia is not an Islamic State is the meaning of the signs contained in the selected 7 frame are talkinh about religious values. From the data obtained by use of the analysis the author signs contained in the movie by semiotics theory Charles Sanders Peirce. The analysis is done through two stages, namely the significance of picture/ frame then the results will be used as the material for the next stage of analysis i.e intrepretation contextually. Construction of taht menaing-laden will appear in the form of pictures an footage of the scene is also a narrative speaker which is considered to represent the intent of film’s director, Jason Iskandar. Religious values taht appear in the film include recognition of the personal rightts of each human being as the basis for understanding cross-cultural diffrerences, religious beliefs and social development, the concept of community-based “Agree in Disagreement”. The existence of the guarantee of a secure, peaceful, get along well, and serene as the foundation running philosophical values of Pancasila.